Analisis Saluran dan Margin Pemasaran Komoditas Beras Ketan di Kota Surabaya: Analysis of Marketing Channels and Margins for Glutinous Rice Commodities in the city of Surabaya - Mubarokah, Mubarokah; Dewi, Erika Triana (Jurnal Ilmiah Manajemen Agribisnis, 2023)
One of the strategic and essential commodities in fulfilling human needs is sticky rice. High price fluctuations, weak people's purchasing power, and problems at the producer level are crucial, including long marketing chains and high marketing margins. This research aims to analyze sticky rice marketing channels and marketing margins in the city of Surabaya. Location selection was carried out using purposive sampling technique and sample selection using snowball sampling technique. The research results show that the marketing channel for sticky rice in the city of Surabaya has one channel, starting from Producers - Wholesalers - Retailers - Consumers. The results of marketing margin analysis show that wholesalers have the highest margin value with a margin value of 3,500/Kg. However, the largest share distribution is in retail trading institutions with a value of 64.50% with a profit to cost ratio of 1.32.